Ionosphere-thermosphere coupling via global-scale waves: new insights from two-years of concurrent in situ and remotely-sensed satellite observations - Gasperini, Federico; Harding, Brian J.; Crowley, Geoffrey; Immel, Thomas J. (Frontiers in Astronomy and Space Sciences, 2023)
Growing evidence indicates that a selected group of global-scale waves from the lower atmosphere constitute a significant source of ionosphere-thermosphere (IT, 100-600 km) variability. Due to the geometry of the magnetic field lines, this IT coupling occurs mainly at low latitudes (< 30 • ) and is driven by waves originating in the tropical troposphere such as the diurnal eastward propagating tide with zonal wave number s = -3 (DE3) and the quasi-3-day ultra-fast Kelvin wave with s = -1 (UFKW1). In this work, over 2 years of simultaneous in situ ion densities from Ion Velocity Meters (IVMs) onboard the Ionospheric Connection Explorer (ICON) near 590 km and the Scintillation Observations and Response of the Ionosphere to Electrodynamics (SORTIE) CubeSat near 420 km, along with remotely-sensed lower (ca. 105 km) and middle (ca. 220 km) thermospheric horizontal winds from ICON's Michelson Interferometer for Global High-resolution Thermospheric Imaging (MIGHTI) are employed to demonstrate a rich spectrum of waves coupling these IT regions. Strong DE3 and UFKW1 topside ionospheric variations are traced to lower thermospheric zonal winds, while large diurnal s = 2 (DW2) and zonally symmetric (D0) variations are traced to middle thermospheric winds generated in situ. Analyses of diurnal tides from the Climatological Tidal Model of the Thermosphere (CTMT) reveal general agreement near 105 km, with larger discrepancies near 220 km due to in situ tidal generation not captured by CTMT. This study highlights the utility of simultaneous satellite measurements for studies of IT coupling via global-scale waves.